Risk of Ankylosing Spondylitis in Patients With Endometriosis: A Population-Based Retrospective Cohort Study - Yin, Zhihua; Low, Hui-Ying; Chen, Brian Shiian; Huang, Kuo-Shu; Zhang, Yue; Wang, Yu-Hsun; Ye, Zhizhong; Wei, James Cheng-Chung (Frontiers in Immunology, 2022)
Objectives: Previous research showed the possible relationship between endometriosis and autoimmune diseases. However, the relationship between endometriosis and ankylosing spondylitis (AS) is lacking. Therefore, we intended to find possible associations between endometriosis and AS using ICD-9 coding data in a population-based retrospective cohort study in Taiwan. Method: Data for this retrospective cohort study were collected during 2000–2012 from the Taiwan National Health Insurance Research Database (NHIRD). We collected 13145 patients with endometriosis and 78870 non-endometriosis controls. Diagnoses of endometriosis and AS were defined by the International Classification of Diseases-9 (ICD-9-CM) code for at least 3 outpatient or 1 hospitalization. Propensity score matching by comorbidities, corticosteroids and non-steroidal anti-inflammatory drugs (NSAIDs) usage were done for baseline comparability. Cox proportional hazard models were used to evaluate crude and adjusted hazard ratios. Results: Cumulative incidence of AS was higher in patients with endometriosis compared to non-endometriosis controls (log-rank test, p=0.015). The adjusted hazard ratio (aHR) of incidental AS in patients with endometriosis was 1.61 (95% CI=1.11 to 2.35) in comparison to the non-endometriosis controls. Increased risk of AS was also observed in subjects with major depressive disorder (aHR= 5.05, 95% CI=1.85 to 13.78). Stratified analyses on age subgroups showed consistent results. NSAIDs users had lower risk of AS than NSAIDs non-users (aHR 4.57 vs 1.35, p for interaction=0.031). Conclusions: In this retrospective population-based cohort study, we found a higher risk of AS in patients with endometriosis. We suggest that clinicians should pay attention to the occurrence of AS in patients with endometriosis.